Pelatihan Pengembangan Kecakapan Sosial Anak Usia Dini melalui Pembelajaran Deep Learning di TK YPK Harapan Abepura: Pengabdian - Fitriani, Fitriani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Social skills development is a fundamental aspect of early childhood education, as it forms the basis for children’s ability to interact, collaborate, empathize, and regulate emotions. However, learning practices in many early childhood education settings remain activity-oriented and have not adequately facilitated the systematic development of children’s social skills. This community service program aimed to implement training on social skills development through deep learning-based instruction at TK YPK Harapan Abepura. The program employed a participatory and collaborative approach, positioning teachers as active participants. The stages included needs analysis, training on social skills and deep learning concepts, mentoring in lesson planning and classroom implementation, and reflective evaluation. Data were collected through observations, interviews, and documentation and analyzed using descriptive qualitative methods. The results indicated a significant improvement in teachers’ understanding and pedagogical competence in designing learning activities that explicitly target social skills development. The implementation of deep learning-based instruction positively influenced classroom dynamics, as evidenced by increased cooperation, communication, empathy, and emotional regulation among children.